MELT GENERATION BY ISENTROPIC MANTLE UPWELLING - Iwamori H.; McKenzie D.; Takahashi E. (My University, 1995)
The primary effects of melt segregation processes on isentropic melting paths are studied using a one-dimensional steady-state model. A parameterization of X(T',P) to 9 GPa shows that X, the degree of melting, depends on pressure, as well as on T', the homologous temperature. Simple scaling analyses show that local thermal equilibrium is likely in the mantle, irrespective of the mechanism of melt transport. If the melt is transported through sparsely distributed paths, it is chemically isolated from the residue and fractional melting occurs. In this case the solidus and liquidus temperatures increase as melt is removed. These changes decrease the degree of melting at a given potential temperature and pressure by between 5 and 15%, compared to the case where no chemical isolation occurs. Therefore the mantle potential temperature required to produce an oceanic crustal thickness of 7 km is higher, by perhaps 20-30°, if it is generated by fractional rather than by batch melting. If no chemical isolation occurs, H2O-undersaturated melt percolating upwards solidifies in the pressure ranges 2.9-2.7 GPa and 0.03-0.0 GPa, where dTP of the solidus curve is negative. When the melt is chemically isolated, the absence of melting in these two pressure ranges causes the melt to be produced in two zones at different depths. This behaviour may account for some features of subduction zone magmatism. Although the principal features of the melting paths for batch and fractional melting under dry and hydrous conditions are now clear, more experimental data on P-T-X relationships are required to obtain accurate estimates of the melting paths, especially for fractional and hydrous melting.